Gender differences in the expression of erythrocyte aggregation in relation to Bβ-fibrinogen gene polymorphisms in apparently healthy individuals - Assayag, Einor Ben; Bova, Irena; Berliner, Shlomo; Peretz, Hava; Usher, Sali; Shapira, Itzhak; Bornstein, Natan M. (Thrombosis and Haemostasis, 2006)
An increased erythrocyte aggregation (EA) is associated with capillary slow flow, tissue hypoxemia and endothelial dysfunction. Fibrinogen is a major determinant in the formation of aggregated red blood cells. It has been suggested that the Bβ-fibrinogen –455G/A polymorphism is associated with erythrocyte hyperaggregability in men with coronary artery disease.The purpose of this study was to investigate the influence of the β-fibrinogen –455G/A polymorphism on erythrocyte aggregation in apparently healthy individuals. Plasma fibrinogen, red blood cell count, serum lipids, erythrocyte sedimentation rate, and the genotype of the Bβ-fibrinogen –455G/A polymorphism were examined in a cohort of 545 apparently healthy individuals and those with atherothrombotic risk factors. A whole blood erythrocyte aggregation test was performed by using a simple slide test and image analysis. In men, EA levels and plasma fibrinogen levels were significantly higher in subjects carrying the –455A allele compared to subjects with the –455 GG genotype.This association did not exist in women carrying the fibrinogen –455A allele.The –455GA/AA men presented significantly higher correlation between the plasma fibrinogen concentrations and EA. This observation raises the prospect of possible change in the functional properties of the –455GA/AA fibrinogen, enhancing its ability to induce EH. This study suggests that the Bβ-fibrinogen –455A allele is related to EH in men only. Putative mechanism could be hyperfibrinogenemia anda functional change in the fibrinogen molecule that alters its ability to interact with red blood cells and supports the aggregability of these cells.
Keywords: Erythrocyte aggregation; fibrinogen; gene polymorphism